7. Kerja Sama Pemerintah Nigeria dengan UNICEF dalam Rangka Menangani Perdagangan Anak di Nigeria - Anisa Nur Rahmah; Tri Cahyo Utomo; Nadia Farabi (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2017)
Nigeria is an African country notorious for human trafficking across its borders.Trafficking in Nigeria is one of the biggest crimes after economic fraud and drugtrafficking. Victims of human trafficking in Nigeria are mostly children; this is becausetheir families have to deal with a number of economic constraints, for instance low wages,which make them more vulnerable to being trafficked. To overcome the problem, theUNICEF has been mandated by the UN to assist Nigeria in applying the internationalchild rights convention to combat the problem of child trafficking in there. In 2003,UNICEF and the Government of Nigeria agreed on the Child Rights Act, which is used asthe basis for addressing the problem of child trafficking. As a descriptive study, thisresearch aims to describe the phenomenon of child trafficking in Nigeria and gives anoverview of cooperation by the government of Nigeria with UNICEF in order to handlethat problem. This study would like to observe the Nigerian government's cooperation withUNICEF in addressing child trafficking in Nigeria. The cooperation between theGovernment of Nigeria with UNICEF related to child trafficking generates the ChildRights Act (CRA), which becomes the foundation of the rights of the child, as well as theprotection of the children.